The Effect of Intrinsic Motivation and Competence on Employee Performance: Study at a Toll Road Development and Operator Company in Bandung - Dani Permana; Nenny Rinawati; Titi Titi; Tini Supartini (Majalah Bisnis & IPTEK, 2023)
This study aims to ascertain how intrinsic motivation and skilfulness affect employee performance in one of Bandung's highway development and operation enterprises. Both descriptive and verificative research techniques are employed. A sample of 39 employees from one of the highway development and operation companies in Bandung were polled to gather data and information for the study. It is clear from the research's path analysis findings that the intrinsic motivation variable (X1) has a favourable impact on employee performance (Y). Employee performance (Y) is positively influenced by the competence variable (X2). According to the conclusions and recommendations drawn from the research, management should preserve and enhance motivation and competence.